The Oral Commensal Streptococcus mitis Shows a Mixed Memory Th Cell Signature That Is Similar to and Cross-Reactive with Streptococcus pneumoniae - Engen, Stian André (Public Library of Science, 2014)

(untitled)
BACKGROUND: Carriage of and infection with Streptococcus pneumoniae is known to predominantly induce T helper 17 (Th17) responses in humans, but the types of Th cells showing reactivity towards commensal streptococci with low pathogenic potential, such as the oral commensals S. mitis and S. salivarius, remain uncharacterized. METHODS: Memory CD4(+) T helper (Th) cell subsets were isolated from healthy human blood donors according to differential expression of chemokine receptors, expanded in vitro using polyclonal stimuli and characterized for reactivity against different streptococcal strains. RESULTS: Th cells responding to S. mitis, S. salivarius and S. pneumoniae were predominantly in a CCR6(+)CXCR3(+) subset and produced IFN-γ, and in a CCR6(+)CCR4(+) subset and produced IL-17 and IL-22. Frequencies of S. pneumoniae-reactive Th cells were higher than frequencies of S. mitis- and S. salivarius-specific Th cells. S. mitis and S. pneumoniae isogenic capsule knock-out mutants and a S. mitis mutant expressing the serotype 4 capsule of S. pneumoniae showed no different Th cell responses as compared to wild type strains. S. mitis-specific Th17 cells showed cross-reactivity with S. pneumoniae. CONCLUSIONS: As Th17 cells partly control clearance of S. pneumoniae, cross-reactive Th17 cells that may be induced by commensal bacterial species may influence the immune response, independent of capsule expression.